Human Papillomavirus and Vaccination in Cervical Cancer - Kung-Liahng Wang (Elsevier, 2007)
Cervical cancer is not only the most frequently reported cancer among women, but also the most common female genital tract neoplasm in Taiwan. Early detection is effective, because the development, maintenance and progression of precursor lesions (cervical intraepithelial neoplasia [CIN]) evolve slowly into invasive cancer, typically over a period of more than 10 years. It is now recognized that human papillomavirus (HPV) infection is a necessary cause for over 99% of cervical cancer cases. Advances in the understanding of the causative role of HPV in the etiology of high-grade cervical lesions (CIN 2/3) and cervical cancer have led to the development, evaluation and recommendation of HPV-based technologies for cervical cancer prevention and control. The prevention of HPV infection before the onset of CIN is now possible with recently available prophylactic HPV vaccines, e.g. the quadrivalent Gardasil (Merck & Co., NJ, USA) and bivalent Cervarix (GlaxoSmithKline, London, UK). This review article provides an up-to-date summary of recent studies and available information concerning HPV and vaccination in cervical cancer.